Efficacy and safety of alirocumab in individuals with type 2 diabetes mellitus with or without mixed dyslipidaemia: Analysis of the ODYSSEY LONG TERM trial. (September 2018) - Taskinen, Marja-Riitta; Del Prato, Stefano; Bujas-Bobanovic, Maja; Louie, Michael J.; Letierce, Alexia; Thompson, Desmond; Colhoun, Helen M.
Abstract: Background and aims: Alirocumab, a monoclonal antibody to proprotein convertase subtilisin/kexin type 9, significantly reduces low-density lipoprotein cholesterol (LDL-C). We evaluated the efficacy and safety of alirocumab in individuals with type 2 diabetes mellitus (T2DM) with versus without mixed dyslipidaemia (MDL, defined as baseline LDL-C ≥70 mg/dL [1.8 mmol/L] and triglycerides ≥150 mg/dL [1.7 mmol/L]). Methods: Data from 812 individuals with T2DM, from the placebo-controlled, 78-week, Phase 3 ODYSSEY LONG TERM trial of alirocumab 150 mg every 2 weeks (Q2W), on a background of maximally tolerated statins ± other lipid-lowering therapies, were pooled according to MDL status. Efficacy endpoints included percentage change from baseline to Week 24 in calculated LDL-C and other lipids/lipoproteins. Results: In individuals with T2DM who received alirocumab 150 mg Q2W, mean LDL-C changes from baseline to Week 24 were −62.6% ( vs . −6.0% with placebo) in those with MDL and −56.1% ( vs . 5.6%) in those without MDL, with no significant between-group difference ( p -interaction = 0.0842). Risk-based LDL-C goals (<70 [1.8 mmol/L] or <100 mg/dL [2.6 mmol/L]) were achieved by 69.1% and 72.4% of alirocumab-treated individuals with and without MDL, respectively. Mean reductions in non-high-density lipoprotein cholesterol (49.2% and 47.8%) and apolipoprotein B (50.2% and 49.1%) with alirocumab were also similar in those with and without MDL, respectively. Treatment-emergent adverse event rates were comparable between alirocumab-treated individuals with T2DM, with and without MDL. Conclusions: Reductions in LDL-C and other lipids with alirocumab, as well as safety and tolerability, were comparable between individuals with T2DM and with versus without MDL. Graphical abstract: Image 1 Highlights: Individuals with T2DM and mixed dyslipidaemia (MDL) are at very high CV risk. This is a subanalysis of LONG TERM, a Phase 3 randomized placebo-controlled trial. In T2DM ± MDL alirocumab significantly reduced atherogenic lipid/lipoprotein levels. Alirocumab's safety profile was favourable in subjects with T2DM with/without MDL.